Productivity change of Portuguese municipalities after local reforms. Issue 12 (12th July 2017) - Aparicio, Juan; Cordero, Jose M.; Pastor, Jesus T.
ABSTRACT: This article examines the impact of the reforms introduced in the structure of the Portuguese local administration after the bailout agreement in 2011 on the efficiency and productivity of municipalities. In order to determine a measure of productivity change, we apply the global Malmquist productivity index to assess the performance of the 278 Portuguese mainland municipalities for the recent 6-year period 2009–2014. The overall results reveal that there was a decrease in the global productivity until 2013 followed by a notable increase in 2014 basically due to technological changes, thus it seems that the reforms have had a positive effect on the productivity of municipalities.